2014
DOI: 10.1242/dev.105775
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic regulatory network explains ParaHox gene control of gut patterning in the sea urchin

Abstract: The anteroposterior patterning of the embryonic gut represents one of the most intriguing biological processes in development. A dynamic control of gene transcription regulation and cell movement is perfectly orchestrated to shape a functional gut in distinct specialized parts. Two ParaHox genes, Xlox and Cdx, play key roles in vertebrate and sea urchin gut patterning through molecular mechanisms that are still mostly unclear. Here, we have combined functional analysis methodologies with high-resolution imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 64 publications
2
38
0
Order By: Relevance
“…Lox morphants are seen to have a disorganized musculature in the foregut region and partial digestive function. Along with Parahox transcription factor, Cdx, circuitry of a GRN for gut regionalization is being uncovered (Annunziata & Arnone, 2014; Annunziata et al, 2014; Cole et al, 2009). What is necessary is to connect those known upstream regulators to the explicit cell behaviors they control.…”
Section: Discussionmentioning
confidence: 99%
“…Lox morphants are seen to have a disorganized musculature in the foregut region and partial digestive function. Along with Parahox transcription factor, Cdx, circuitry of a GRN for gut regionalization is being uncovered (Annunziata & Arnone, 2014; Annunziata et al, 2014; Cole et al, 2009). What is necessary is to connect those known upstream regulators to the explicit cell behaviors they control.…”
Section: Discussionmentioning
confidence: 99%
“…underlying development (27)(28)(29)(30). It has been shown that FGF signalling is 6 necessary for guiding skeletogenic mesenchymal cell migration and formation 7 of the embryonic skeleton in the sea urchin Paracentrotus lividus (31).…”
Section: Introductionmentioning
confidence: 99%
“…Previous gene regulatory studies reveal that endoderm specification is well underway in 24‐h embryos (Peter & Davidson ) and that tripartite gut subdivision occurs past the 24‐h stage (Arenas‐Mena et al . ; Annunziata & Arnone ). When H2A.Z inhibition is triggered in 24‐h embryos, endoderm formation and gastrulation proceeds normally, but tripartite gut subdivision is absent (Fig.…”
Section: Discussionmentioning
confidence: 99%